Diet Quality and Past Changes in Food Consumption as Determinants of Intentions to Eat Less Meat and More Plant-Based Foods - Marzena Jeżewska-Zychowicz; Marta Sajdakowska; Jerzy Gębski; Małgorzata Kosicka-Gębska; Krystyna Gutkowska (Foods)
This study aimed to examine the relationship between self-reported changes in food consumption over the past 2 years, quality of actual diet, and declared intentions to eat more plant-based foods while reducing meat consumption in the next year. A cross-sectional study using Computer-Assisted Web Interview (CAWI) was conducted on 1003 Polish adults in 2023. The Beliefs and Eating Habits Questionnaire (KomPAN) was used to assess the frequency of consuming various food groups and to calculate diet quality indices. Four distinct segments (“No change”, “All products limited”, “Changes in meat”, and “Less red meat, more other products”) were identified using cluster analysis. Logistic regression analysis verified the associations between these clusters, diet quality indices, and intended changes in plant-based food and meat consumption. The study results showed that most pre-existing changes involved reduced red meat intake (52%). The “No change” cluster (47.9%) was represented by more men, people with lower education, and those with a lower overall dietary quality index (DQI). A higher quality diet (as indicated by the DQI) was associated with a greater tendency to increase plant food consumption and reduce meat consumption across the entire group and within each cluster. A better understanding of how changes in food consumption relate to diet quality and intended changes in plant-based food and meat consumption can inform interventions promoting sustainable consumption, considering both nutritional recommendations and environmental requirements.